House prices and interest rates: Bayesian evidence from Germany - Christoph Hanck; Jan Prüser (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2016)
This study uses a Bayesian VAR to demonstrate that the recent house price boom in Germany can be explained by falling interest rates and that higher interest rates are likely suciffient to stop the increase of German house prices. The latter suggests a potential drawback of the current monetary policy of the ECB. The BVAR's prior information shrinks the model parameters towards a parsimonious benchmark. We provide a simulation study to compare the frequentist properties of two useful strategies to select the informativeness of the prior. The study reveals that prior information helps to obtain more precise estimates of impulse response functions in small samples. To choose relevant control variables, we use a new Bayesian variable selection approach by Ding and Karlsson (2014). In addition to impulse responses and variance decompositions, we use a Bayesian conditional forecast to test the hypothetical effect of an increase of interest rates on house prices. This approach has the crucial advantage that it is invariant to the ordering of the variables. – – Diese Studie verwendet ein Bayesianisches VAR (BVAR), um zu zeigen, dass der jüngste Hauspreisboom in Deutschland durch fallende Zinsen erklärt werden kann und dass ein höheres Zinsniveau wahrscheinlich zu einem Ende des Booms führen würde. Dies impliziert einen potentiellen Nachteil der aktuellen Geldpolitik der EZB. Die a priori Information schrumpft die BVAR Modellparameter in Richtung eines naiven Benchmarks. In einer Simulationsstudie vergleichen wir die frequentistischen Eigenschaften von zwei nützlichen Strategien, um den Informationsgehalt des Priors zu wählen. Die Studie zeigt, dass a priori Informationen helfen können, um präzisere Schätzungen von Impuls-Antwort-Funktionen in kleinen Stichproben zu erhalten. Um die relevanten Kontrollvariablen auszuwählen, verwenden wir ein neues Bayesianisches Variablen Auswahlverfahren von Ding und Karlsson (2014). Neben Impuls-Antwort-Funktionen und Varianzzerlegungen benutzen wir Bayesianische bedingte Prognosen, um den hypothetischen Effekt von steigenden Zinsen auf Häuserpreise zu analysieren. Dieser Ansatz hat den entscheidenden Vorteil, nicht von der Anordnung der Variablen abhängig zu sein.
Keywords: C11; C32; C53; E37; E43; 330; Bayesian VAR; shrinkage; house prices